2005
DOI: 10.1016/j.intfin.2004.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Financial markets and economic growth in Greece, 1986–1999

Abstract: This paper assesses empirically the relationship between the development of the banking system and the stock market and economic performance for the case of Greece over the period 1986-1999. Greece is a medium sized EU country where the financial liberalization process started back in the early eighties. The empirical results, using VAR models, suggest that there exists a bi-directional causality between finance and growth in the long run. The findings, using error-correction models, show that both bank and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(77 citation statements)
references
References 53 publications
5
66
0
1
Order By: Relevance
“…Some of the most important studies in this area are Angelini and Cetorelli (2003) and Maudos and Fernández de Guevara (2004). 17 This index involves the econometric estimation of a total revenue function with input prices as explanatory variables. The summation of the relevant coefficients provides the value of the index.…”
Section: Concentrationmentioning
confidence: 99%
“…Some of the most important studies in this area are Angelini and Cetorelli (2003) and Maudos and Fernández de Guevara (2004). 17 This index involves the econometric estimation of a total revenue function with input prices as explanatory variables. The summation of the relevant coefficients provides the value of the index.…”
Section: Concentrationmentioning
confidence: 99%
“…Os resultados encontrados corroboram com outras pesquisas que não encontraram evidências efetivas entre o desempenho do mercado de ações com a inovação tecnológica e o crescimento econômico, tais como: (ARESTIS; DEMETRIADES; LUINTEL, 2001;BECK, 2003;HOOK, 2004;ZHU, ASH;POLLIN, 2004;LEVINE, 2004;DRITSAKI;DRITSAKI-BARGIOTA, 2005;HONDROYIANNIS;LOLOS;PAPAPETROU, 2005;BEM-NACEUR;GHAZOUANI, 2007;PILO, 2012;KUOSMANEN;VATAJA, 2013;FLORACKIS, et al, 2014;AHMED;MMOLAINYANE, 2014;ODHIAMBO, 2014).…”
Section: Considerações Finaisunclassified
“…They stress out to build the reliable financial system to experience the economic growth of the country. Hondroyiannis, et al (2005) [15] found by conducting study in Greece that the relationship between capital market and economic growth are bi-directional in the long run even though both stock market and banks can endorse economic growth but their effects are small. Ergungor (2008) stated that countries which follow inflexible judicial system have significance effect on economic growth by banking sector where in the flexible judicial system capital market has strong effect on economic growth.…”
Section: Capital Market and Economic Growthmentioning
confidence: 99%